Carbon quantum dot-covered porous Ag with enhanced activity for selective electroreduction of CO2 to CO. Issue 6 (30th April 2019) - Gao, Jin; Zhao, Siqi; Guo, Sijie; Wang, Huibo; Sun, Yue; Yao, Bowen; Liu, Yang; Huang, Hui; Kang, Zhenhui
Abstract : A carbon quantum dot-covered porous Ag composite can efficiently reduce CO2 to CO. Abstract : Ag is a promising efficient catalyst for selective electroreduction of CO2 to CO. However, challenges such as high overpotential and poor stability for Ag in CO2 electroreduction still remain unsolved. In this work, we demonstrate that a carbon quantum dot (CQD)-covered porous Ag (p-Ag/CQD) composite can efficiently reduce CO2 to CO with a maximum CO faradaic efficiency of 83.2% at the potential of −0.8 V ( vs. RHE). The p-Ag/CQD composite exhibits a 6.3-fold and 20.8-fold enhancement of CO current density relative to porous Ag and Ag foil, respectively, and shows a more stable current density during the 4 h electrolysis. The dramatically enhanced catalytic activity of the p-Ag/CQD composite should be ascribed to its porous structure and the existence of CQDs on its surface. The existing CQDs can improve the abilities of CO2 adsorption/CO desorption and stabilize the CO2 − intermediate to achieve a lower overpotential compared with porous Ag and Ag foil. More importantly, the synergistic effect of porous Ag and CQDs has a significant catalytic effect on the CO2 reduction reaction.